Strategi Bertahan Kegiatan Pemasaran Home Industry YUAN Di Masa Pandemi Covid-19 - Susi Putri Ayu Lestari; Mardiyah Hayati (Universitas Islam Kadiri, 2023)
Sales of business units have decreased due to the implementation of Large -Scale Social Restrictions (PSBB) by the government as an effort to suppress the spread of Covid-19 so that business units including â€œYUANâ€ industrial home-owners are required to consider post-pandemic marketing strategies to restore the economic condition of their business. Therefore, the aim of this study is (1) to analyze the existing strategy of YUANâ€™s home industry marketing; (2) to analyze the marketing strategy of YUANâ€™s home industry after the covid-19 pandemic; (3) to determine the priority of the marketing mix strategy after the covid-19 pandemic. The data analysis method used this research is STP analysis, marketing mix and Analytical Hierarchy Process. The results showed that (1) the owner has implemented segmenting, targeting, positioning, and marketing mix strategy however it does not reach the optimal; (2) the owner needs to evaluate the previous marketing strategies; (3) the priority of the marketing mix strategy after the covid-19 pandemic is distribution or place strategy.